2018
DOI: 10.1016/j.pmedr.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Response to reduced nicotine content cigarettes among smokers with chronic health conditions

Abstract: Individuals with chronic health conditions persist in smoking despite the presence of smoking-related illness. The aim of this study was to examine whether chronic health conditions moderate response to reduced nicotine content cigarettes (0.4, 2.4, 5.2, 15.8 mg/g of tobacco). This is a secondary analysis of a controlled clinical laboratory study that examined the acute effects of cigarettes varying in nicotine content among individuals especially vulnerable to smoking and tobacco dependence. Participants in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Consistent with the previous literature (see, e.g., Higgins et al 2018;Nighbor et al 2020;Smith et al 2017;Streck et al 2018;Weidberg et al 2018), the reduction in tobacco use resulted in a decrease in cigarette demand, specifically in O max and intensity of demand. Furthermore, this finding is congruent with others indicating that individuals with greater tobacco use show a higher cigarette demand (González-Roz et al 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with the previous literature (see, e.g., Higgins et al 2018;Nighbor et al 2020;Smith et al 2017;Streck et al 2018;Weidberg et al 2018), the reduction in tobacco use resulted in a decrease in cigarette demand, specifically in O max and intensity of demand. Furthermore, this finding is congruent with others indicating that individuals with greater tobacco use show a higher cigarette demand (González-Roz et al 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, even though there is evidence that motivation to quit in smokers with schizophrenia spectrum disorders is quite similar to those of smokers without mental illness, it is evident that it is more difficult to help them to quit (Streck et al, 2018). Therefore, additional effective strategies of traditional cigarette smoking cessation, reduction and THR approach are needed.…”
Section: Motivation To Quit Smoking In the General Population And Motivation To Quit Smoking In People With Schizophrenia Spectrum Disordmentioning
confidence: 99%
“…A prior study showed that people who smoke with chronic health conditions experienced the same responses to reduced nicotine cigarettes as individuals without these conditions. 33 Third, we were not able to verify adherence to only smoking study cigarettes and in fact, participants reported using approximately one additional non-study cigarette per day throughout the VLNC vs. NNC condition. It is possible that a more profound effect of reducing nicotine in cigarettes might be observed if conventional nicotine cigarettes were unavailable.…”
Section: Discussionmentioning
confidence: 92%